Early treatment of neonatal diabetes with oral glibenclamide in an extremely preterm infant. Issue 2 (29th January 2023) - Galderisi, Alfonso; Kermorvant‐Duchemin, Elsa; Daruich, Alejandra; Bonnard, Adeline Alice; Lapillonne, Alexandre; Aubelle, Marie‐Stéphanie; Perrella, Bruna; Vial, Yoann; Cave, Héléne; Berdugo, Marianne; Jarreau, Pierre‐Henri; Polak, Michel; et al.
Abstract: Early treatment of neonatal diabetes with sulfonylureas has been proven to produce marked improvements of neurodevelopment, beside the demonstrated efficacy on glycemic control. Several barriers still prevent an early treatment in preterm babies including the limited availability of suitable galenic form of glibenclamide. We adopted oral glibenclamide suspension (Amglidia) for the early treatment of neonatal diabetes due to an homozygous variant of KCNJ11 gene c.10C>T [p.Arg4Cys] in an extremely preterm infant born at 26 + 2 weeks' of gestational age. After ~6 weeks of insulin treatment with a low glucose intake (4.5 g/kg/day), the infant was switched to Amglidia 6 mg/ml diluted in maternal milk, via nasogastric tube (0.2 mg/kg/day) progressively reduced to 0.01 mg/kg/day (after ~3 months). While on glibenclamide, the patient exhibited a mean daily growth of 11 g/kg/day. The treatment was suspended at month 6 of birth (weight 4.9 kg [5th–10th centile], M3 of c.a.) for normalization of glucose profile. During the treatment, the patient exhibited a stable glucose profile within the range of 4–8 mmol/L in the absence of hypo or hyperglycemic episodes with 2–3 blood glucose tests per day. The patient was diagnosed with retinopathy of prematurity Stade II in Zone II without plus disease at 32 weeks, with progressive regression and complete retinal vascularization at 6 months of birth. Amglidia could be regarded as the specific treatment for neonatal diabetes even in preterm babies due to its beneficial effect on the metabolic and neurodevelopmental side.